Ta`līm al-Qawā`id an-Naḥwiyyah Bi aṭ-Ṭarīqah al-Istiqrāiyyah `Alā Asās al-Madkhal al-`Ilmī Bi Ma`had al-Muhājirīn Aceh Besar - M. Alfi Syahril; Hilmi Hilmi; Intan Afriati (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
Arabic has two grammars, nahwu, and sharaf. Nahwu specializes in the rule of changing word endings, while Sharaf focuses on word changes. The use of nahwu helps with determining each function of every word in a sentence, the adjustment of word endings, and their positions. Therefore, nahwu is fundamental in learning Arabic. When learning activities took place in the female class VII- A at Junior High School Al-Muhajirin, the initial process was conducive. The teacher taught students by applying the istiqraiyah method. However, the situation in the classroom changed after 30 minutes, especially for students sitting in the back. Some of them ate snacks, talked to each other, and fluttered using books although the room’s temperature was normal. The circumstance happened because the learning activity was teacher-centered, the teacher was more active than the students. This study aimed to apply the Istiqraiyah method based on the scientific approach in learning nahwu, to find out students' responses on the application of the method and to know the influences of the istiqraiyah method based on the scientific approach in grammar learning in each cycle. The researcher applied the classroom action research (PTK). The population of this study was 172 students. The study sample was female students in class IX-a. There were 36 students. The researcher carried out observations, and tests, and provided questionnaires. The findings of this study were: 1) The implementation of the istiqraiyah method based on the scientific approach was very effective. The teacher observation result in the second circle (94,21%) was higher than the first circle (89,47%). The student observation result in the second circle (93,75%) was higher than the first circle (88, 75%). 2) The students’ responses to the istiqraiyah method based on the scientific approach in learning the nahwu grammatical structure at Dayah Al-Muhajirin were very good. The result of the students' responses in the second circle (86, 11%) was higher than the first one (79,73%). 3) The influences of the istiqraiyah method based on the scientific approach in the nahwu grammar learning at Dayah Al-Muhajirin were effective in improving students' nahwu grammatical skills. The result of the student test in the first cycle (70, 31%) was higher than the test in the pre-cycle (46, 25%). The result of the student test in the second cycle (84,37%) was higher than the student test in the first cycle (70,31%).